ARIMA Model to Predict Fully Vaccinated People Against Covid-19 in Several Province in Indonesia - Rini Yanti; Wirta Agustin; Torkis Nasution (STMIK PONTIANAK, 2022)
WHO was declared Corona Virus Desease 19 (Covid-19) as a global pandemic because of its massive and uncontrol spread. First case was occurred in Wuhan on December 2019 and was detected in Indonesia on early March 2020 in Depok, West Java.Vaccines was the most effective to control infectious desease. Vaccination against Covid-19 in Indonesia started in January 2021. In this study, the number of people in Kepulauan Bangka Belitung, Kepulauan Riau, DI Yogyakarta, Kalimantan Utara and Maluku with fully vaccinated was forecasted using Auto Regressive Integrated Moving Average (ARIMA) models. The models show that on 31 December 2021, Bangka Belitung, Kepulauan Riau, DI Yogyakarta, Kalimantan Utara and Maluku will reach 47.75%, 60.58%, 70.96%, 44.84%, 36.21% and 17.83% of the province population will be fully vaccinated. The results can estimate when the province reach the herd immunity treshold level.